Scrutinizing The "Green Constitution" Idea in The Amendment of The 1945 Constitution - Adi Gunawan; Achmad Taufik (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
Environmental degradation has reached an alarming stage with the increasing number of natural disasters in Indonesia and various states. Such conditions at present require the State to take concrete steps to deal with more massive disasters in the future. The primary concrete step the State can take is to include specific environmental protection issues in the state constitution because environmental matters in the existing 1945 Constitution cannot provide maximum environmental protection. This research objective was to provide a juridical conceptual idea based on a study of principles and theories by comparing facts in several other states. Furthermore, the research method was juridical-normative, and the research design was legally dogmatic. This research used secondary data, which was then analyzed and presented qualitatively. The research results showed that environmental regulations in the 1945 Constitution are no longer relevant and can no longer provide environmental protection and preservation. Therefore, in the amendments to the 1945 Constitution concerning the environment, immediate attention must be given to establishing a government agency that explicitly handles environmental preservation with provisions aimed at realizing a green constitution.